Crime and Punishment in Latin America : Law and Society Since Late Colonial Times - Joseph, G. M. (Gilbert Michael), 1947-; Aguirre, Carlos, 1958-; Salvatore, Ricardo Donato (Book collections on Project MUSE., 2001)
Essays in collection argue that Latin American legal institutions were both mechanisms of social control and unique arenas for ordinary people to contest government policies and resist exploitation.